2007
DOI: 10.1038/sj.clpt.6100312
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Meropenem Determined by Microdialysis in the Peritoneal Fluid of Patients With Severe Peritonitis Associated With Septic Shock

Abstract: Our objective was to describe the pharmacokinetics of meropenem in the peritoneal fluid (PF) of six patients with severe peritonitis and septic shock and to relate measured concentrations to the minimum inhibitory concentration of bacteria. Microdialysis catheters were placed into the peritoneal space during surgery. Meropenem concentrations in plasma and in PF were analyzed using compartmental modeling. Meropenem areas under the concentration-time curve were lower in PF than in plasma (average ratio, 73.8+/-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 28 publications
(50 reference statements)
8
48
0
Order By: Relevance
“…The penetration of meropenem into peritoneal fluid was rapid, the exposures were roughly comparable to those in plasma, and the between-patient variability of F PF was relatively small (Table 2). The estimated extent of penetration into peritoneal fluid (F PF ) in our study was in good agreement with previously reported estimates that ranged from 0.74 to 1.0 (32,33).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The penetration of meropenem into peritoneal fluid was rapid, the exposures were roughly comparable to those in plasma, and the between-patient variability of F PF was relatively small (Table 2). The estimated extent of penetration into peritoneal fluid (F PF ) in our study was in good agreement with previously reported estimates that ranged from 0.74 to 1.0 (32,33).…”
Section: Discussionsupporting
confidence: 81%
“…2; Table 2). Previous studies on the penetration of meropenem into subcutaneous tissue and peritoneal fluid showed rapid equilibration after the end of the infusion (31,33). Our sampling times ensured that we could adequately characterize the terminal phase and, therefore, the fT ϾMIC .…”
Section: Discussionmentioning
confidence: 99%
“…via a microdialysis technique. Meropenem areas under the concentration-time curve in peritoneal fluid reached 73.8% (SD, Ϯ15%) of plasma levels and were thus only slightly lower than in the blood (16). Of interest, the degradation of meropenem ex vivo in the peritoneal fluid was also demonstrated.…”
Section: Discussionmentioning
confidence: 82%
“…The in vivo relative recovery by loss was calculated for each dialysate collected, and the mean value was used to correct the dialysate concentrations (19). The metronidazole residual unbound concentration in brain was taken into consideration to estimate recovery, as previously described (20). Briefly, in vivo recovery was calculated for each interval as presented in the following equation: in vivo recovery ϭ [(C in ϩ C ext ) Ϫ C out ]/C in , where C in and C out are the perfusate and dialysate metronidazole concentrations and C ext is the extrapolated concentration of metronidazole in the dialysate at the midpoint of the retrodialysis interval of collection.…”
Section: Methodsmentioning
confidence: 99%